Uma proposta para ensinar os conceitos da análise combinatória e de probabilidade: uma aplicação do uso da história da matemática, como organizador prévio, e dos mapas conceituais - BOGA NETO, Francisco Rodrigues (2005)
We discussed, in this work, a proposal of use of the history of the mathematics, as previous organizer, for the teaching of the combination analysis and of the probability. That use of the history of the mathematics has as objective to develop the knowledge subsumers, presents in the students' cognitive structure, so that it can happen, in a significant way, the learning of the concepts of those topics of the mathematics, and that they will be taught, in a more detailed way, later on, through the conceptual maps. It is worth to stand out that, the previous organizers' of the content use, as well as the theory of the conceptual maps, they have theoretical justification in the works on significant learning, of the educational psychologist David P. Ausubel.